Validation of the Computational Fluid Dynamics (CFD) Method for Predicting Wind Flow Around a High-Rise Building (HRB) in an Urban Boundary Layer Condition - Sapian, Abdul Razak (Penerbit Universiti Sains Malaysia, 2009)
Virtual Experiments or, more specifically, the Computational Fluid Dynamics (CFD) method have been used in numerous airflow studies. Most CFD code providers claim that their software can simulate and model airflow around a building. However, the literature shows little or no evidence of the implementation of this software for this purpose. Therefore, this study attempts to validate and justify the reliability of this software, by investigating the wind flow around a high-rise building. The main goal of this paper is to determine if the CFD method can be used to study wind flow around a high-rise building, with a focus on the effect natural cross ventilation within a building to predict the indoor air velocity, for human thermal comfort purposes. A software called FloVent from Flomeric Inc. UK was used in the experiments. The data obtained from the simulation are compared with wind tunnel data. The result of the analysis shows that the deviation between the CFD and wind tunnel data is less than 15% on average. This result indicates that the CFD can be used as an alternative method for investigating wind flow around high-rise buildings in an urban boundary layer condition.